2015
DOI: 10.26491/mhwm/42201
|View full text |Cite
|
Sign up to set email alerts
|

Desalination of Groundwater and Impoundments using Nano-Zero Valent Iron, n-Fe0

Abstract: Salinization of groundwater is a major problem, particularly in areas with limited infrastructure. 14 diffusion reactors are operated diabatically at-8°C to 20°C to determine the amount of NaCl removed by n-Fe 0. The reac-1 ]. Desalination commences at a time, t, after the n-Fe 0 is added to the water, and continues with an exponential decline until a base (equilibrium) salinity is reached. The effectiveness of n-Fe 0 as a desalination agent appears to increase with increased water salinity. Placement of PSN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…It has been suggested [190] that during desalination the Fe corrosion products behave as electrochemical, switchable, redox moieties, where the initial Fe The presence of purple FeOOH species ( Figure F1) is indicative of Na inclusion. Na inclusion can take the form (e.g., Figure C37), 2FeOOH + 2 NaO − = Fe(OH)2 + Na2FeO4 + 2e − [251].…”
Section: Appendix H Identification Of the Radicals Involved In Nacl mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested [190] that during desalination the Fe corrosion products behave as electrochemical, switchable, redox moieties, where the initial Fe The presence of purple FeOOH species ( Figure F1) is indicative of Na inclusion. Na inclusion can take the form (e.g., Figure C37), 2FeOOH + 2 NaO − = Fe(OH)2 + Na2FeO4 + 2e − [251].…”
Section: Appendix H Identification Of the Radicals Involved In Nacl mentioning
confidence: 99%
“…ZVI desalination has been associated with a high surface area [20,21,25,190], indicating that the contact area between the Fe 0 and water surface is important [15,18,191,192]. Experiments using Fe + organic chemicals have demonstrated [5,6,[193][194][195][196][197][198][199][200] that increases in water salinity are associated with in an increase in the rate of degradation of the organic chemicals and (COx, HxCyOz).…”
Section: Economic Implications Of Corrosion Scalementioning
confidence: 99%
“…This technology places ZVI-derived products (e.g., pellets, or granules, or powders) [1,2] in a static body of water (e.g., an existing tank (Figure 1), pond or impoundment). The ZVI concentration is within the range of 0.3-90 g¨ZVI¨L [1,2].…”
Section: Static Diffusion Zvi Partial Desalinationmentioning
confidence: 99%
“…Desalination associated with zero valent iron (ZVI, Fe 0 ) has been demonstrated in more than 160 batch trials (utilizing 0.2-240 L/batch [1][2][3][4][5]) and by monitoring the salinity of water flowing through granular Fe 0 permeable reactive barriers (PRB) [6][7][8][9][10]. These trials have demonstrated that ZVI desalination has potential applications for groundwater management, road runoff water management, agricultural water management, municipal and domestic water, emergency and disaster water requirements, feed and waste water treatment associated with conventional desalination plants, waste water associated with the extractive industries and environmental damage mitigation [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation